2014
DOI: 10.1101/002352
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SNP-guided identification of monoallelic DNA-methylation events from enrichment-based sequencing data

Abstract: ABSTRACT

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 52 publications
1
6
0
3
Order By: Relevance
“…However, the downside of this methodology is that non-imprinted genes may also show monoallelic expression [1,26], and imprinted expression is mostly tissue-specific [20,27]. Another approach that has been extensively explored is the search for epigenetic signature of imprinted regions, using methylation microarrays or next generation sequencing [11][12][13]15,16,18]. Although methylation array does not provide data of allelic methylation, the advantage of this approach is that, in most tissues, DNA methylation of IGs is preserved throughout development and adult life, irrespective of their expression status [3,24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the downside of this methodology is that non-imprinted genes may also show monoallelic expression [1,26], and imprinted expression is mostly tissue-specific [20,27]. Another approach that has been extensively explored is the search for epigenetic signature of imprinted regions, using methylation microarrays or next generation sequencing [11][12][13]15,16,18]. Although methylation array does not provide data of allelic methylation, the advantage of this approach is that, in most tissues, DNA methylation of IGs is preserved throughout development and adult life, irrespective of their expression status [3,24].…”
Section: Discussionmentioning
confidence: 99%
“…We compared the high-throughput imprinting studies in human reported since 2011 (Table S3) [11][12][13][14][15][16][17][18][19][20]. Different methods were designed to screen novel candidate IGs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrasting previous genome-wide methods, no DNA genotyping data is required, as we solely rely on genotyping of RNA-seq data. The basic rationale is that in case of 100% imprinting, no heterozygous samples can be found in RNA-seq data, as they perfectly resemble homozygous samples (only a single allele is expressed) (see Methods section and Steyaert et al 27 ). The established imprinting model describes the data for each SNP as a mixture of homozygous and heterozygous samples, more specifically as a mixture of genotype dependent binomial distributions, with weights derived from Hardy-Weinberg equilibrium.…”
Section: Detection Of Imprinting In Healthy Breast Tissuementioning
confidence: 99%